وسيلة الرسوم الهزلية (Komik) استخدام في تعليم مهارة القراءة - J Sutarjo (Institut Agama Islam Negeri (IAIN) Metro, 2017)
Reading is on of the for skills tought in every foreign language teaching. It’s included to Arabic teaching in Indonesia as Muslim Language and foreign language for Indonesian. Arabic text it’s self is not interesting for students couse of the difference especially the letters and lingustics. Of course it needs the innovetions in running the teaching. For the young leaners comic is on of reading the students interested on. This writing concerns to describe about the comic as a media in teaching Arabic especially in reading. Understanding comic as a media in teaching Arabic starting from the concept of the comic, comic as a teaching media, applying teaching especially in reading Arabic text, and the benefits and the shortages of comic as teacing media. As the kind of reading, comic is very famous of the young people. Almost all of the children already have read it in their daily reading activities. Because of the interest of the children it is become a chance for the teachers to use this kind of reading to be an economical media and make the teaching more effective.